2012
DOI: 10.1126/science.1220961
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastrointestinal Infection Induces Long-Lived Microbiota-Specific T Cell Responses

Abstract: The mammalian gastrointestinal tract contains a large and diverse population of commensal bacteria and is also one of the primary sites of exposure to pathogens. How the immune system perceives commensals in the context of mucosal infection is unclear. Here we show that during a gastrointestinal infection, tolerance to commensals is lost and microbiota-specific T cells are activated and differentiate to inflammatory effector cells. Furthermore, these T cells go on to form memory cells that are phenotypically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
317
4
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(344 citation statements)
references
References 31 publications
15
317
4
4
Order By: Relevance
“…Interestingly, T. gondii exposure is a well-documented risk factor for schizophrenia [83,84], and as a gut pathogen is a tool used in experimental models to produce an inflammatory state in the GI tract. Thus not surprisingly, T. gondii infection can drive the dysbiosis of resident microbial communities and bring about a state of increased GI permeability [85][86][87][88]. In our studies of clinical samples, we found correlations between levels of T. gondii IgG with food antigen IgG in people with a recent onset of schizophrenia, which were not present in control groups [13].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 53%
“…Interestingly, T. gondii exposure is a well-documented risk factor for schizophrenia [83,84], and as a gut pathogen is a tool used in experimental models to produce an inflammatory state in the GI tract. Thus not surprisingly, T. gondii infection can drive the dysbiosis of resident microbial communities and bring about a state of increased GI permeability [85][86][87][88]. In our studies of clinical samples, we found correlations between levels of T. gondii IgG with food antigen IgG in people with a recent onset of schizophrenia, which were not present in control groups [13].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 53%
“…39,40 Correlated with this observation, peritoneal cavity T-cell populations have also been demonstrated to have an antigen-experienced/memory phenotype but with low frequency of Foxp3 1 Treg cells. 41 These findings indicate that to maintain intestinal homeostasis and tightly control the activated T cells, peritoneal B-1a might have an unexplored role on intestinal homeostasis that presents gut antigen to generate Treg cells. However, in the in vivo environment, other professional APCs, such as peritoneal DCs, might compete for antigen, and the frequency at which B-1a cells contact CD4 1 T cells might be relatively low compared with the in vitro culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly little is known about how T. gondii behaves in the small intestine of orally infected hosts. There are isolated reports of dividing parasites in intestinal tissue 1 d after infection (dpi), and the parasite increases in number in the small intestine between 3 and 7 dpi (2,(4)(5)(6)9). However, we lack basic information concerning the distribution of parasites in the small intestine during the first week of infection and how this distribution…”
Section: Spatial and Temporal Pattern Of T Gondii Infection In The Imentioning
confidence: 99%
“…This model is useful to further our understanding of host-pathogen interactions in the intestine and of common mechanisms underpinning the development of inflammatory bowel disease (3). Nevertheless, we have limited understanding of how and in which cells infection is established in the intestine, the extent to which the parasite replicates and spreads within the intestine, and how these factors contribute to the development of pathology (2,(4)(5)(6)(7)(8)(9). The ability to label living parasites fluorescently and track them in the tissues of infected hosts provides an important tool for investigating these questions (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%